2001
DOI: 10.1002/1097-0142(20010415)91:8<1458::aid-cncr1153>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of intracranial and spinal tumors in patients with Down syndrome and report of a rapidly progressing Grade 2 astrocytoma

Abstract: BACKGROUND Brain tumors in patients with Down syndrome (DS) rarely are reported, and their behavior is not well known. METHODS The authors report on a male patient age 19 years who had DS with diffuse astrocytoma (World Health Organization Grade 2) that recurred twice despite treatment, leading to a glioblastoma and, finally, to death in just over 2 years. The literature on brain tumors in patients with DS is reviewed. RESULTS Although brain neoplasms were suspected to be in excess in patients with DS, the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Most studies have suggested a decreased incidence of intracranial tumors. 9,20-23 Thirty-eight reported cases with intracranial and spinal tumors were summarized by Satgé et al 24 In our study, two (1 month of age and 6 years of age) out of three cases with central nervous system tumors were identified as germ cell tumors (…”
Section: Central Nervous System Tumorsmentioning
confidence: 66%
See 1 more Smart Citation
“…Most studies have suggested a decreased incidence of intracranial tumors. 9,20-23 Thirty-eight reported cases with intracranial and spinal tumors were summarized by Satgé et al 24 In our study, two (1 month of age and 6 years of age) out of three cases with central nervous system tumors were identified as germ cell tumors (…”
Section: Central Nervous System Tumorsmentioning
confidence: 66%
“…Satgé et al . reported that 14 (61%) of 23 cases under age 15 were classified as germ cell tumors 24 …”
Section: Discussionmentioning
confidence: 99%
“…[1117] In cases of Down syndrome, the proportion of germ cell tumors is quite high reaching to 61% of all intracranial tumors associated with this disease. [13] However, association of teratoma with Down syndrome is quite rare. We only found four cases of this type including ours, three of them being Japanese [Table 1].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest an excess of luteinizing hormone and follicle-stimulating gonadotropin caused by cryptorchidism[14] or inherent genetic changes associated with this disease relate to the tumorigenesis. [113]…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of a particular form of germ cell tumor in a neonate with trisomy 21 is in agreement with the growing evidence that gonadal and extragonadal germ cell tumors are more frequent in DS. This is particularly true for the retroperitoneal area and the cranium, where FIF are usually found 4−6 …”
mentioning
confidence: 98%